An empirical investigation of buyer–supplier relationship typologies and their behavioral and performance outcomes. Issue 4 (4th August 2021) - Li, Jin; Chai, Linlin; Tangpong, Chanchai; Hong, Michelle; Traub, Rodney D.
Abstract : Purpose: This study aims to examine empirically the existence of four classical and four emerging buyer–supplier relationship (BSR) types and how they differ in terms of behavioral dynamics and performance measures. Design/methodology/approach: This study uses an online survey to collect data from 371 purchasing managers in the USA. Findings: A cluster analysis statistically supports the existence of five of these eight BSR types, including strategic/bilateral partnership, market/discrete, supplier-led collaboration, captive supplier/buyer dominant and captive buyer/supplier dominant BSRs. Further, ANOVA tests show that these five BSRs differ in terms of behavioral outcomes and performance measures. Research limitations/implications: This study is based on a cross-sectional survey so it cannot examine how these BSR types may evolve over time, and it is not suitable to examine some rare types of BSRs. In addition, this study does not consider contextual factors that may moderate the influence of BSR types on the behavioral dynamics and performance measures. Practical implications: Managers should consider the potential to be able to develop and enhance a strategic/bilateral relationship with their supply chain partners, which in at least some circumstances can lead to superior performance results. Similar observations can be made with respect to supplier-led and, to a lesser degree, buyer-led collaboration. Originality/value: Most existing research of the BSR types is largely a product of theoretical classifications, and there is also a lack of research of their performance implications. This study fills these gaps in the literature.